Diversity of play - Fuchs, Mathias (meson press, 2015)
Abstract: The early days when digital games were new, harmless, and a niche are long gone. Today's games can simulate battlefields, predict disaster, and crash markets. We are faced with a diversity of play and the ubiquity of games, making them not only a popular medium, but the leading medium of our contemporary society. Based on the keynote lectures held at DiGRA2015,
10.14619/012
Keywords: Konferenzschrift; (thesoz)Computerspiel; (thesoz)Spiel; (thesoz)Digitalisierung; (thesoz)Simulation; (thesoz)Medienkritik; (thesoz)interaktive Medien; Gamification; Play Studies; Game Studies; Gothic; Narratology; Ludology; Ludification; Diversity; DiGRA